Teachers' Perceptions in Implementing Technologies In Language Teaching and Learning in Indonesia - Katemba, Caroline Victorine (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2020)
Technologies have swept the world in every aspect of life including the education system. And therefore, the purpose of this research is to find the Challenges Encountered in implementing technologies in Language Teaching and Learning in Indonesia. This study was a quantitative method in nature. The participants of the study were randomly chosen 30 teachers from Bandung in the rural area. The data were collected by using questionnaires and were analyzed by using mix method that is quantitative and qualitative procedures. The result showed that using technology in the classroom was helpful. In addition to that, more tools and facilities provided by schools are increasingly helping them improve their ability to use technology. Though the school has prepared facilities there were several challenges found in the implementation of technologies in the Language Learning classrooms. Additional results of this study give meaningful insights for policymakers in relation to the implementation of ICT for teaching and learning in the classroom.